Climatology and numerical case study of moisture sources associated with subtropical cyclogenesis over the southwestern Atlantic Ocean - Gozzo, L. F. [UNESP]; Rocha, R. P. da; Gimeno, L.; Drumond, A. (Amer Geophysical Union, 2017)
An important feature during cyclogenesis is the availability of moisture to fuel the associated convective activity providing faster developments and more intense systems. In this work, an investigation of the role of local evaporation and remote water vapor transport prior to subtropical cyclogenesis in the southwestern South Atlantic (named RG1 region) is presented. Results were obtained analyzing the period from 1980 to 2015 with a Lagrangian particle dispersion model together with the ERA-Interim reanalysis. The northern sector of the Subtropical High in the South Atlantic Ocean stands out as the main source region of water vapor to the RG1, with the low-level northeasterly winds being responsible by moisture transport. An anomalous moisture transport from lower latitudes preceded the subtropical cyclogenesis events and provided the necessary water vapor to fuel the convective activity. A numerical case study using the Weather Research and Forecasting mesoscale model indicated that the remote moisture source is essential for subtropical cyclogenesis in RG1, since it allows a stronger surface low pressure to develop and supports the formation of a cutoff low in the middle troposphere. Though the local evaporation has a secondary role in this process, it helped the system to attain the observed intensity and subtropical characteristics. Therefore, both local and remote moisture sources provide the incipient subtropical cyclone with the horizontal temperature advection and convective activity necessary to its further development.
Keywords: subtropical cyclones; local versus remote moisture sources; Lagrangian analysis; conditions for cyclogenesis